2019
DOI: 10.1542/peds.2018-0387
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Clinical Care Algorithm to Improve Care for Children With Hematogenous Osteomyelitis

Abstract: Acute hematogenous osteomyelitis (AHO) causes significant morbidity in children 1 -3 and often requires prolonged and costly treatment. 1, 3 -6 A recent large study from Spain revealed that children with osteomyelitis were hospitalized for an average of 13.5 days, that 20% required surgery, and that 2.3% developed longterm sequelae, such as leg-length discrepancy. 3 Early transition to oral therapy has been shown to be an effective and less costly approach compared with prolonged parenteral therapy. 5 -13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Surgical debridement has historically been controversial. While some recent evidence has emerged demonstrating that early aggressive surgical source control may be beneficial, other authors have shown higher rates of chronic osteomyelitis following aggressive primary surgery (5,9,10). Various surgical techniques have been described in the literature including abscess drainage and debridement, osseous drilling and the spilt-heel technique (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical debridement has historically been controversial. While some recent evidence has emerged demonstrating that early aggressive surgical source control may be beneficial, other authors have shown higher rates of chronic osteomyelitis following aggressive primary surgery (5,9,10). Various surgical techniques have been described in the literature including abscess drainage and debridement, osseous drilling and the spilt-heel technique (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Hasta en un 30% de niños (sobre todo neonatos [70% de los casos] y menores de 18 meses) coexisten con osteomielitis aguda y artritis séptica, especialmente en hombro y cadera por la existencia de metáfisis intraarticular (8). Un estudio reciente realizado en España reveló que los niños con osteomielitis e554 fueron hospitalizados por un promedio de 13.5 días, que el 20% requirió cirugía y que el 2.3% desarrolló secuelas a largo plazo, como la discrepancia en la longitud de las piernas (12). Se ha descrito un aumento del número de casos de osteomielitis aguda de hasta 2,8 veces en los últimos 20 años lo que podría deberse a la mejora de las técnicas diagnósticas (11).…”
Section: Epidemiologíaunclassified
“…[15][16][17] Previous quality improvement (QI) studies have revealed improved patient outcomes or process measures through clinical algorithms for osteomyelitis and/or septic arthritis. [18][19][20][21][22] These studies may have been limited by small sample sizes and/or use of pre-post analysis without additional methods to account for temporal trends. 23,24 We aimed to improve the care of patients with MSKI at our organization through 4 QI interventions: (1) infectious disease (ID) provider education, (2) centralization of admission location, (3) coordination of radiology-orthopedic communication, and (4) application of a MSKI algorithm and order set.…”
mentioning
confidence: 99%